2017
DOI: 10.1371/journal.pone.0171561
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of extrapolative factors linked with oxidative injury and anti-inflammatory status in chronic kidney disease patients experiencing cardiovascular distress

Abstract: BackgroundChronic kidney disease (CKD) is a group of heterogeneous abnormalities affecting the function and structure of the kidney and mostly further proceeds to cardiovascular damage prior to end stage renal disease (ESRD). The oxidative insult and inflammatory mediators have some undefined role in CKD and cardiovascular complications. It is therefore, aimed at to pin point the predictive factors in the development of cardiovascular disorder in patients with chronic kidney disease.MethodsFifty patients of CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…As the prevalence of older age is higher among patients with urothelial carcinoma, studies report a recent increase in interest in the impact of preoperative renal insufficiency on poor prognosis [13][14][15]24,25]. Several studies have indicated an association between chronic kidney disease (CKD) and oncological outcomes associated with the effects of chronic inflammation, oxidative stress, metabolic disorder, uraemiaassociated immune deficiency, and frailty [26][27][28]. However, an association between the severity of renal insufficiency and malignant potential in urothelial carcinoma remains to be established, and only a few studies have evaluated the impact of preoperative eGFR < 45 ml/min/1.73 m 2 on oncological outcomes in patients with urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of older age is higher among patients with urothelial carcinoma, studies report a recent increase in interest in the impact of preoperative renal insufficiency on poor prognosis [13][14][15]24,25]. Several studies have indicated an association between chronic kidney disease (CKD) and oncological outcomes associated with the effects of chronic inflammation, oxidative stress, metabolic disorder, uraemiaassociated immune deficiency, and frailty [26][27][28]. However, an association between the severity of renal insufficiency and malignant potential in urothelial carcinoma remains to be established, and only a few studies have evaluated the impact of preoperative eGFR < 45 ml/min/1.73 m 2 on oncological outcomes in patients with urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a strong correlation between preoperative CKD and poor prognosis, suggesting that the CKD patients with urothelial carcinoma might have aggressive cancer behavior leading to disease progression and recurrence. In general, CKD is strongly associated with all-cause mortality, especially in cardiovascular-related mortality [ 21 ]. Therefore, it is not surprising that the number of patients with CVD was higher in the pre-CKD group in the present study (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for the strong association between CKD and cancer recurrence and mortality remains undetermined. Although there is no clear explanation, the effects of metabolic syndrome [ 22 ] and chronic inflammation may explain the association of CKD and oncological outcome [ 21 , 23 ]. Immunocompromised CKD patients may have reduced DNA repair capacity and protection against viral oncogene [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, excessive expression of iNOS can be disadvantageous, for example, during sepsis. The adverse action of NO is associated with the production of superoxide anions and subsequent generation of peroxynitrite and hydroxyl radicals, which are highly toxic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%